Oral cavity and lip cancer: United Kingdom National Multidisciplinary Guidelines - Kerawala, C (J Laryngol Otol, 2016)
This is the official guideline endorsed by the specialty associations involved in the care of head and neck cancer patients in the UK. It provides recommendations on the assessment and management of patients with cancer of the oral cavity and the lip. RECOMMENDATIONS: • Surgery remains the mainstay of management for oral cavity tumours. (R) • Tumour resection should be performed with a clinical clearance of 1 cm vital structures permitting. (R) • Elective neck treatment should be offered for all oral cavity tumours. (R) • Adjuvant radiochemotherapy in the presence of advanced neck disease or positive margins improves control rates. (R) • Early stage lip cancer can be treated equally well by surgery or radiation therapy. (R)